GENETIC ANALYSIS OF SOME POLYGENIC TRAITS FOR DROUGHT TOLERANCE IN GOSSYPIUM HIRSUTUM L. - ! A. Rehman; M. T. Azhar; A. Shakeel; S. M. A. Basra (Journal of Animal and Plant Sciences, 2018)
The present study was conducted to develop high yielding cotton genotypes having desirable fiber quality traits under water stress conditions. Ten upland cotton genotypes were identified as drought tolerant whereas six as drought susceptible based on root and shoot related traits. These sixteen genotypes were grown in the field conditions and crossed following line ×tester mating fashion. In the next cotton season, these sixty hybrids along with parents were grown in the field conditions. Analysis of variance revealed the presence of significant differences among the genotypes for all of the traits i.e., boll weight, ginning out turn, fiber length, fiber strength and fiber fineness. Further, the lines i.e., NIAB-111, CP-15/2, CIM-482 and CIM-446, and testers i.e., CIM-506, FH-1000 and MNH-129 had better performance under drought conditions. The cross combinations viz., CIM-707 × S-12, CIM-707 × NIAB Karishma, CIM-707, CIM- 446 × NIAB Karishma, CIM-446 × S-12, and CRIS-134 × S-12 were also identified as best specific combinations and superior for yield contributing parameters. These cross combinations may be exploited on large scale for the development of new germplasm of upland cotton suitable for planting under drought conditions of the Punjab. conditions. The pattern of inheritance of ginning out-turn
Keywords: Gossypium hirsutum L.; Genetic analysis; Line × Tester; Water stress.